INTERAKSI ANTARA MASYARAKAT DAN KAWASAN HUTAN KPH LINDUNG RINJANI BARAT, NUSA TENGGARA BARAT - Tri Sulistyati Widyaningsih; Devy Priambodo Kuswantoro; Suyarno Suyarno (Balai Litbang Teknologi Agroforestry, Ciamis, 2019)
Communities around the Rinjani Barat Protected Forest Management Unit (PFMU) have used the forest to fulfil economic needs before the area was designated as an FMU in 2009. This study aims to obtain information about community dependence of Rinjani Barat PFMU forest area. The study was conducted from August to November 2015 by interviewing 130 respondents and FGD with 80 persons from villages around the PFMU area, namely Pusuk Lestari, Kekait, and Buwun Sejati in Lombok Barat Regency and Tegal Maja Village in Lombok Utara Regency, Nusa Tenggara Barat (NTB) Province. Community dependence on forests is measured by the parameters of land-based work, the frequency of community activities in the forest, the arable land area in the forest, the distance of residence to the forest, and the utilization of forest products. The data collected on each parameter were given 1-4 score and added up. The results showed that Kekait Village community has moderate dependence (score 8), Pusuk Lestari, Tegal Maja and Buwun Sejati Villages community have high dependence on Rinjani Barat PFMU forest area with scores of 11, 11, and 15, respectively. Some of majority people work land-based as farmers, do activities in the forest, have arable land in the forest of 0.4-0.9 ha, live around the forest area with a distance of 2-7 km, and use forest products to fulfil the needs of firewood, food, medicine, and animal feed. Community dependence on forests needs to be directed at protective measures so that forest resources remain sustainable and beneficial for many parties.